Targeted microbiome-sparing antibiotics. Issue 9 (September 2021) - Avis, Tim; Wilson, Francis X.; Khan, Nawaz; Mason, Clive S.; Powell, David J.
Abstract: A factor in our inability to meet the challenge of clinical antibiotic resistance has been the low productivity of research and development (R&D) efforts, with only incremental improvements on existing broad-spectrum classes coming into clinical use recently. The disappointing returns from this approach have focussed attention on narrower-spectrum antibiotics; such new agents are directed against the pathogen of relevance with the additional benefit of preserving the human microbiome(s). Our knowledge of the gut microbiome and its contribution to health homeostasis increases yearly and suggests that broad-spectrum treatments incur health costs beyond the initial infection. Improved diagnostics, antibiotic stewardship, and the crucial role of the gut microbiome in health indicate targeted agents as a more viable approach for future antibiotic R&D.